Local tourists perception on how effective is malacca zoo as an ecotourism destination - Taarini A/P Sockalingam (2012)
The main objectives of this study were to identify the factors the influence the effectiveness of Malacca Zoo as an ecotourism destination. The variables which are included in this research are conservation, education, recreational and entertainment as the independent variables and sustaining Malacca Zoo as an ecotourism is the dependent variable. For this objectives the method used was a survey questionnaire which consist two parts, first to measure the demographic factors and second part for independent variables and dependent variable. The survey were participated by 100 respondent of local tourist who have visited Malacca Zoo before, there were the studies sample. As for the result, analysis was conducted using Statistical Package for the Social Science (SPSS)version 16.0 to determine the reliability and validity of the questionnaire. From the findings, the result shows that overall all the independent variable are significant in sustaining Malacca Zoo as an ecotourism destination. All result was obtained using the correlation coefficient and they were all positive result. Correlation result for conservation (r=0.695**, p=0.000), education (r=0.566**, p=0.000), recreational (r=0.592**, p=0.000) and entertainment (r=0.327**, p=0.001) where it shows effectiveness of sustaining Malacca Zoo.